Rate dependence of early afterdepolarizations in the His-Purkinje system: A simulation study. (April 2022) - Geng, Zihui; Jin, Lian; Huang, Yanqi; Wu, Xiaomei
Highlights: Revealing the rate dependence of EADs in the His-Purkinje system and its effect on ventricular electrical activities. The subcellular key factors x-gate is an important mechanism involved to the rate dependence of EADs in the His-Purkinje system. The rate dependence of EADs lead to the left and right ventricular alternating excitation. In a certain stimulation cycle length window, chaos behaviors of EADs will be observed in the His-Purkinje system. Abstract: Background and Objective: Early afterdepolarizations (EADs) are associated with a variety of arrhythmias and have the property of rate dependence. EADs can occur in Purkinje cells while the effect of rate dependence of EADs in the His-Purkinje system has not been fully investigated. In order to reveal the rate dependence of EADs in the His-Purkinje system and its effect on ventricular electrical activities, the simulation research was carried out in this manuscript. Methods: This manuscript first studied the relationship between the occurrence of EADs and stimulation cycle length on the DiFranNoble cell model. Then, the relationship between the rate dependence of EADs and the conduction block of the His-Purkinje system at slow heart rates was studied on the rabbit whole ventricular model including the His-Purkinje system, and its mechanism was analyzed from multiple angles. Results: ① The rate dependence of EADs is related to the inconsistency of EADs occurrence in the His-Purkinje system. When the stimulation cycle length is long or short enough, EADs either occur or not occur stably in the His-Purkinje system, while in a certain stimulation cycle length window, the chaotic state of EADs will be observed. ② The key subcellular factors x-gate is an important mechanism involved to the rate dependence of EADs in the His-Purkinje system. ③ The discrete distribution of x-gate values and the "source-sink" mechanism lead to the inconsistency of EADs in the His-Purkinje system. The prolonged action potential duration caused by EADs can lead to conduction block at slow heart rates. Conclusion: The rate dependence of EADs in Purkinje system can lead to disordered ventricular electrical activity.